Kleinia (Asteraceae): comprehensive review of ethnomedicinal uses, phytochemical profiles, ethnopharmacological applications, and toxicological insights - Tegegne, Bantayehu Addis; Begashaw, Tesfa; Belay, Wubetu Yihunie; Tariku, Mengistie Kassahun; Zeleke, Tirsit Ketsela; Jemal, Mohammed; Getinet, Mamaru; Alehegn, Agumas Alemu; Dagne, Abebe (Frontiers in Pharmacology, 2025)
Kleinia is a genus of over 50 species that are commonly used in primary care in several countries. This study seeks to inspire researchers to quickly discover and isolate the key active metabolites found in Kleinia taxa, thereby promoting the development of novel, safe, and effective therapies for a variety of illnesses. To this end, we performed a thorough search of English-language publications from PubMed, Scopus, ScienceDirect, Web of Science, Google Scholar, and ResearchGate. Our search utilized keywords such as “ethnobotany,” “geographic distribution,” “ethnomedicinal use,” “phytochemistry,” “pharmacological or bioactivities,” and “toxicological activities” related to the genus Kleinia. Chemical structures were depicted using Chemdraw® software. Literature highlights numerous Kleinia taxa used in traditional medicine for conditions like intestinal parasites, measles, smallpox, diabetes, edema, nerve disorders, sexual dysfunction, gastrointestinal issues, cancer and more. Phytochemical analysis identifies 77 secondary metabolites, mainly alkaloids, flavonoids, saponins, terpenes, and terpenoids and other miscellaneous metabolites. Among the Kleinia taxa, K. anteuphorbium, K. longiflora, K. grandiflora, K. odora, K. squarrosa, K. abyssinica, K. pendula, and K. azoides have been scientifically validated to exhibit various pharmacological activities. However, the existence of potentially harmful metabolites in Kleinia taxa, particularly pyrrolizidine alkaloids, emphasizes the significance of cautious application in traditional medicine and the need for rigorous toxicological assessments. In conclusion, this review highlights the promise of Kleinia taxa as significant medicinal resources and advocates for extensive bioprospecting. It encourages global pharmaceutical companies and academic institutions to conduct thorough investigations of the genus Kleinia to uncover new therapeutic possibilities.